Doskonalenie warsztatu metodycznego nauczyciela języka specjalistycznego w kontekście kształcenia nieformalnego. Wyniki badania pilotażowego - Wojakowska , Marta (Neofilolog, 2024)
The importance of foreign language skills has increased in the labor market in recent years. A 2012 survey in Poland shows that effective communication and language skills are the most important skills sought from job applicants. It is therefore not surprising that private language schools and companies are offering more and more foreign language courses for professional purposes. In the context of thinking about informal learning of a language for specific purposes (LSP), it is worth reflecting on how a LSP teacher is prepared for work. It seems that attending workshops or practical training should be part of the repertoire of enhancing the professional competence of LSP teachers. However, discussions with experienced language teachers reveal that the reality is quite different. Therefore, given the growing demand for specialized language courses, diagnosis and discussion of the difficulties faced by LSP teachers is of academic relevance. The first part of this article presents a pilot study conducted in 2023 among LSP teachers. Following this, the difficulties of teaching professional languages will be presented. The last part refers to the presentation of methods, techniques and forms of work that can improve the methodological repertoire of LSP teachers.